Case report: Atypical teratoid/rhabdoid tumor of the lateral ventricle in a male adolescent (case-based review and diagnostic challenges in developing countries) - Karim, Akzhol; Shaikhyzada, Kundyz; Suleimenova, Assel; Ibraimov, Bakytkali; Nurgaliev, Dair; Poddighe, Dimitri (Frontiers in Oncology, 2022)
Atypical teratoid/rhabdoid tumor (AT/RT) is a rare and highly malignant central nervous system (CNS) embryonal neoplasm: it accounts for <2% of all pediatric CNS tumors and occurs mainly in infants and young children. The primary site of this tumor is usually the posterior cranial fossa. Supratentorial and, in detail, latero-ventricular location is extremely uncommon, especially in adolescents. This tumor is characterized by rapid growth and spread in cerebrospinal fluid and, therefore, it is characterized by a poor prognosis. Neurological signs and symptoms are related the location of the tumor. The radiological features of AT/RT are nonspecific. Immunohistochemical staining for loss of nuclear integrase interactor 1 (INI1) expression is considered a reliable criterion for the diagnosis of this type of tumor. AT/RT has been linked to mutations of SMARCB1 or, rarely, SMARCA4 genes, which function as tumor suppressor genes. Currently, there is no validated protocol of treatment for children with AT/RT, and multimodality treatment (consisting of surgery, chemotherapy, and radiation therapy) is considered. In this case report, we describe a 15-year-old adolescent with an AT/RT of the left lateral ventricle. Despite the late diagnosis, the multimodal therapeutic approach provided a good outcome for our patient at 21 months’ follow-up. Based on our case-based review, early diagnosis and a multimodal approach to treatment play a key role in improving the survival of patients with this diagnosis. Implementing a system supporting pathological and molecular analyses for developing countries and, in general, for non-academic centers is of primary importance to timely diagnose and treat rare tumors, such as AT/RT.